The Targeting Benefit of Conditional Cash Transfers - Bergstrom, Katy; Dodds, William (World Bank, Washington, DC, 2020)
Conditional cash transfers (CCTs) are a popular type of social welfare program that make payments to households conditional on human capital investments in children. Compared to unconditional cash transfers (UCTs), CCTs may exclude some low-income households as access is tied to normal investments in children. This paper argues that conditionalities on children's school enrollment offer an unexplored targeting benefit over UCTs: CCTs target money to households that forgo a discrete amount of child income. This paper shows that the size of this targeting benefit is directly related to the distribution of parental incomes, the size of forgone child incomes, and two elasticities already popular in the literature: the income effect of a UCT and the price effect of a CCT. These elasticities are estimated for a large CCT program in rural Mexico, Progresa, using variation in transfers to younger siblings to identify income effects. In this setting, the analysis finds that the targeting benefit is almost as large as the cost of excluding some low-income households; this implies that 41 percent of the Progresa budget should go to a CCT over a UCT based on targeting grounds alone.